Vibration analysis of damaged RC beams strengthened with GFRP. (15th September 2018) - Capozucca, R.
Abstract: The aim of the paper is to investigate the dynamic behaviour of undamaged and damaged reinforced concrete (RC) beams with different constraints: hinged and free-free ends. Two RC beams were analysed experimentally, strengthened with near surface mounted (NSM) glass fibre reinforced polymers (GFRP). One of RC beams was also reinforced with GFRP strips in the compressive zone. Damage of the RC beams was obtained by cracking of concrete for one of the beams, under bending tests, and for the other beam by artificial notches. In this paper, the envelope of Frequency Response Functions (FRFs) obtained by the dynamic experimental tests are shown and the changes of natural frequency values are correlated to the damage degree of beam elements. Finally, modelling of RC beams by finite element method (FEM) is developed for the undamaged beam and for the beam damaged with notches. Experimental results are discussed and a comparison between the experimental results and the theoretical and numerical data obtained is shown.